Verbalization of the concept of the ENEMY in the Ukrainian political discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article analyzes the concept of the enemy as a component of the semantic opposition “our” – “alien”, presented in political communication as one of the main conceptual antinomies. An overview of theoretical works, which highlights the verbalization of the basic concepts of political discourse, representing one of the components of the opposition, is “alien”. The linguistic representations of the enemy concept on the lexical level with the definitions of vocabulary definitions and the philosophical interpretation of the concept are outlined. The verbalization of the concept of the enemy in political discourse was explored on the basis of the speeches and speeches of well-known Ukrainian politicians, which allowed to demonstrate the dynamics of its development and to present the two-component structure of the concept. Concepts that make up the core of the national conceptual sphere are altered primarily by external factors and require additional analysis. First of all, it concerns the semantic opposition, among which the defining place belongs to the conceptual opposition of “our” – “alien”, which in the political discourse is represented in the speeches of political figures, political programs, advertising, etc. One of the verbal representations of the concept of “alien” as a component of semantic opposition is presented in the political communication of the concept of the enemy, which requires a thorough analysis given the relevance of this concept in contemporary political discourse.It is substantiated that in the modern Ukrainian political discourse, the concept of the enemy has a bipolar nuclear part: the first semantic is represented by semantics “ideological enemy”, and the second – “military enemy”. In the first case, it is internal enemies, primarily political opponents, opponents who have opposing or incompatible views. In the second case we are talking about military confrontation, which is represented both in general and in concrete terms. A generalized view of the enemy implies an indication of the presence or active interference by external aggressors, postulating the threat of independence and statehood of Ukraine without indicating the subjects of these hostilities; a concrete presentation implies the actualization of Russia and the Russians as real enemies involved in hostilities against our country. In this case, the semantic field of verbalization is expanding at the expense of the lexem of the thematic group “war”. We fix the domination of the second semantic center of the concept and change the metaphorical models from the family to the militaristic.
Keywords: concept; conceptual opposition; political discourse; semantics; verbalization